Draft genome of Bordetella pseudohinzii BH370 isolated from trachea and lung tissues of a laboratory mouse - Loong, S.K.; Tan, K.K.; Sulaiman, S.; Wong, Pooi Fong; AbuBakar, Sazaly (Elsevier, 2017)
In this study, we present the draft genome sequence of B. pseudohinzii BH370 recovered from the trachea and lung tissues of an ICR mouse in Malaysia. The genome consists of 4,474,040 bp with a GC content of 66.4%. Annotation using RAST algorithm displayed 5119 protein encoding and 52 RNA genes. The CRISPR-cas genomic sequences previously reported in B. pseudohinzii were identified. The nucleotide sequences of BH370 was deposited into the European Nucleotide Archive under the genome assembly accession number FPJN01000000.